Short-term nutrient removal efficiency by Ulva pseudorotundata (Chlorophyta): potential use for Integrated Multi-Trophic Aquaculture (IMTA) - Massocato, Thais Fávero; Robles-Carnero, Victor; Vega, Julia; Bastos, Eduardo; Avilés-Benítez, Antonio; Bonomi-Barufi, José; Rubi Rörig, Leonardo; López-Figueroa, Félix (Springer Nature, 2022)
Short-term N-NH4+ and N-NO3− removal by Ulva pseudorotundata under different initial nutrient concentrations and biomass stocking densities were investigated, monitoring in parallel photosynthetic parameters obtained by Pulse-Amplitude-Modulation (PAM) fluorometry of chlorophyll-a and evaluating biomass characteristics (CHN, proteins, carbohydrates). The results showed that U. pseudorotundata cultivated under solar radiation in a land-based outdoor pilot scale system was efficient in removing N-NH4+ and N-NO3− even in concentrations as high as 500 μmol L–1 ensuring complete water remediation in a period of 24 h and in all experimental conditions tested, however differences were observed depending on the stocking density and type of N-source. reatments with N-NH4+ showed faster N removal than those with N-NO3−, whilst treatments with N-NO3− required more photosynthetic energy. Part of the ammonium removed in the respective treatmentsmay have been volatilized as a combined effect of the pH increase related to photosynthesis and aeration in the tanks. Theresults presented here establish the fundamental parameters for the use of U. pseudorotundata as a biofiltering organism foreffluents with high concentrations of N-NH4+ and N-NO3−
Keywords: Nitrógeno; Fotosíntesis; Algal biomass; Aquaculture; Biofiltration; Chlorophyll-a fluorometry; Nitrogen; Photosynthesis